Dietary Antioxidants May Support Cosmetic Treatment in Patients with Rosacea - Kinga Zujko-Kowalska; Joanna Masłowska; Małgorzata Knaś-Dawidziuk; Jadwiga Hamulka; Małgorzata Elżbieta Zujko (MDPI AG, 2024)
Rosacea is a chronic skin disease that significantly reduces the quality of life (QoL) of patients. The aim of this study was to assess whether dietary antioxidants can support the effect of cosmetic treatment in improving the QoL of patients with rosacea. Basic data about participants (N = 160) were collected using a self-reported survey. QoL was assessed using the standardized Dermatology Life Quality Index (DLQI) questionnaire. An interventional cosmetic treatment was performed using cavitation peeling and sonophoresis with a commercial capillary repair serum. The study was registered as a clinical trial (NCT06271135). To assess antioxidant diet quality, for the first time, a new dietary antioxidant quality index (DAQI) was developed, which consisted of 12 items: dietary total antioxidant capacity, dietary polyphenols, phytosterols, lignans, vitamin C, vitamin E, β-carotene, zinc, iron, copper, manganese and selenium. It was found that the highest tertiles of DAQI diminished the odds about 40-45% of the moderate, large and extremely large effect of rosacea on QoL and about 8-11% of the occurrence of rosacea symptoms compared with the lowest tertile. This study showed that rosacea has a negative impact on QoL, but a comprehensive approach to treatment, including antioxidant cosmetic treatment and dietary antioxidants, can improve the QoL of patients with rosacea.